An Examination of The Significant Frameworks of International Public Sector Accounting Standards (IPSAS) Adoption in Ghana - Richard Kwadzo Doe-Dartey; Jignesh Valand (LAW & PASS: International Journal of Law, Public Administration and Social Studies, 2024)
The purpose of this article is to determine the elements that influence the adoption and use of the International Public Sector Accounting Standards (IPSAS). The study's primary source materials include reviews of several journals, research papers, newspaper articles, magazines, and other official accounting bodies' documentation materials, in addition to conference, seminar, and workshop papers. Based on the study's findings, Ghana must take 10 factors into account before implementing IPSAS. Among them are the following: Acceptable Awareness Level, Associated Adoption Cost, Adequate Technical Capacity, Advanced Education and Experience, Availability of Applicable Expertise, Appreciable Key Management Support, Aggressive External pressure, Adaptation of appropriate technology, Applicable Transition Management, and Active Strategic Planning and Evaluation.